2023
DOI: 10.1021/acs.nanolett.2c04899
|View full text |Cite
|
Sign up to set email alerts
|

Understanding FRET in Upconversion Nanoparticle Nucleic Acid Biosensors

Abstract: Upconversion nanoparticles (UCNPs) have been frequently applied in Forster resonance energy transfer (FRET) bioanalysis. However, the understanding of how surface coatings, bioconjugation, and dye-surface distance influence FRET biosensing performance has not significantly advanced. Here, we investigated UCNPto-dye FRET DNA-hybridization assays in H 2 O and D 2 O using ∼24 nm large NaYF 4 :Yb 3+ ,Er 3+ UCNPs coated with thin layers of silica (SiO 2 ) or poly(acrylic acid) (PAA). FRET resulted in strong distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 70 publications
(102 reference statements)
0
27
0
Order By: Relevance
“…The UCL decay times were not concentration dependent, which is not untypical when UCNPs are used as FRET donors. Recent studies showed that the luminescence decay time is not a reliable parameter for analyzing UCNP-based FRET because the energy stored in the Yb sensitizer ions is continuously transferred to the Er activators during the Er-to-dye FRET process. , Therefore, FRET does not significantly influence the overall decay time that depends on both the incoming and the outgoing energy contributions and is mainly driven by the slow energy transfer from Yb to Er. The assay calibration curves (FRET ratio from eq with donor and acceptor luminescence intensities integrated in a time range from 80 μs to 500 μs after the start of the excitation pulse as a function of DNA 2 -Cy3.5 concentration; Figure C and Figure S8) showed a linear increase over the entire concentration range, demonstrating that the hybridization assays were functional for DNA 2 -Cy3.5 quantification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The UCL decay times were not concentration dependent, which is not untypical when UCNPs are used as FRET donors. Recent studies showed that the luminescence decay time is not a reliable parameter for analyzing UCNP-based FRET because the energy stored in the Yb sensitizer ions is continuously transferred to the Er activators during the Er-to-dye FRET process. , Therefore, FRET does not significantly influence the overall decay time that depends on both the incoming and the outgoing energy contributions and is mainly driven by the slow energy transfer from Yb to Er. The assay calibration curves (FRET ratio from eq with donor and acceptor luminescence intensities integrated in a time range from 80 μs to 500 μs after the start of the excitation pulse as a function of DNA 2 -Cy3.5 concentration; Figure C and Figure S8) showed a linear increase over the entire concentration range, demonstrating that the hybridization assays were functional for DNA 2 -Cy3.5 quantification.…”
Section: Resultsmentioning
confidence: 99%
“…Another important level of complexity is added when UCNPs are applied in biosensing using Förster resonance energy transfer (FRET). , In principle, UCNP-FRET can merge the advantages of UCNPs for biosensing with the high sensitivity and simplicity of wash-free FRET assays. ,, The narrow and tunable emission bands of lanthanoids can be matched with many different FRET acceptors. , Moreover, different strategies for functional bioconjugation of DNA close to the UCNP surface have been developed to respect the strong distance dependence of FRET. ,, Such thin coatings with direct DNA surface attachment have the potential to significantly improve UCNP-based FRET biosensing and bioimaging, which is strongly limited when thick protective shells, such as silica or polymer shells, are used. Considering the importance of different types of DNA and RNA as disease biomarkers, UCNP-FRET is seemingly perfect to answer the increasing demand for nucleic acid based clinical diagnostics. , However, for UCNP-FRET, the energy from the activator ions inside the UCNP must be transferred to suitable FRET acceptors outside the UCNP.…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment, they used UCNP-to-dye FRET DNA-hybridization assays in H 2 O and D 2 O using ~24 nm large NaYF4:Yb 3+ ,Er 3+ UCNPs coated with thin layers of silica (SiO 2 ) or poly(acrylic acid) (PAA). The results showed that UCNPs-to-dye FRET translated into microRNA FRET assay with LOD of 100 fmol [ 46 ]. Nan et al in 2022 discussed the overall properties and uses of several types of nanoparticles in light of the fluorescent nano-biosensor technique for the detection of cancer biomolecular markers.…”
Section: Fret Description Detailsmentioning
confidence: 99%
“…These bands cover a very broad spectral range, ranging from ultraviolet (UV), visible (VIS), and near-infrared (NIR), to short-wave infrared (SWIR). The decay rates of the energy states of lanthanide dopants can be engineered by tailoring the doping level or the structure of the nanoparticles. These strategies have allowed advances in applications of lanthanide-doped luminescent nanoparticles in fields such as nanomedicine, biosensing, clinical diagnostics, super-resolution microscopy, and anticounterfeiting technology. …”
mentioning
confidence: 99%
“…These strategies have allowed advances in applications of lanthanide-doped luminescent nanoparticles in fields such as nanomedicine, biosensing, clinical diagnostics, super-resolution microscopy, and anticounterfeiting technology. 9 16 …”
mentioning
confidence: 99%